1479 Referral of Children from a Uk District General Hospital Emergency Department to Primary Care General Practitioners. (October 2012) - Rowland, AG; Isba, R
Abstract : Background: This preliminary audit aimed to assess the feasibility of referring children presenting to a UK District General Hospital Emergency Department (ED), seeing 27500 children per year, to their own Primary Care General Practitioner (GP) following an initial assessment in the ED. Method: One hundred and fifty-two patients were assessed by a Consultant in Paediatric Emergency Medicine in the ED during the triage process. Those fulfilling the audit inclusion criteria were referred directly from triage to their own off-site Primary Care GP for a same-day assessment. Results: Only ten patients (6.6%) fulfilled the inclusion criteria for referral to Primary Care and seven (70%) of these were accepted, none of whom were referred back to the hospital acutely by their GP. The median time spent in the ED for the 152 patients assessed in the audit was 1 hour 12 minutes and for the 10 patients referred to Primary Care was 31 minutes. Conclusions: Only a small number of children assessed in the audit were suitable for referral to Primary Care. The assessment and referral process was not a good use of Emergency Department resources. The absence of a valid and reliable screening tool or early warning score to predict the safe discharge of children from an ED reduced the number of children that could be referred directly to primary care from the ED. Further multi-centre work is required to evaluate a clinical decision-making framework to enable the accurate assessment of children for their safe discharge or referral from an ED.